Major livestock health problems in market oriented livestock development in Metema woreda, north Gondar Zone, Ethiopia - Bayeleyegn, G. (Addis Ababa University, 2007)
The research was conducted to assess the major animal health problems in market oriented livestock developments and to know the veterinary service in Metema woreda North West of the country from November 2006 to June 2007.A questionnaire survey was conducted in 80 livestock owners to collect information on major livestock health problems, veterinary service of the Woreda and production activities recognized by the farmers in the study area, and supported by group discussions, personal evaluations. Major animal health problems that constraint to be market oriented livestock developments and associated veterinary service are surveyed. These are listed based on the priority of livestock owners and key respondents with their veterinary name and corresponding local name in different age group and the occurrence of the seasons. Major health problems are: In Cattle: LSD, respiratory problem, skin diseases, babesiosis, mastitis and trypanosomosis. In goats and sheep diseases: ORf, respiratory problem, enteritis, pasteurellosis, skin disease. In Poultry: NCD, respiratory problem. In donkey: back sore and respiratory problem. Lack of veterinary service, drugs and vaccines, long distance to get veterinary service, absence of professionals at clinic are major problems.